Isolation and Biochemical Characterization of Ananassains, Cysteine Peptidases from the Fruits of Ananas ananassoides - Okayama, Adriana; Cabral, Hamilton; Gustavo Orlando, Bonilla-Rodriguez (Current Chemical Biology, 2023)
Aims: This work performed a preliminary characterization of two new peptidases from Ananas ananassoides. Background: Proteolytic enzymes, also known as peptidases, are found in all living things and play critical physiological roles in metabolism and cellular regulation. They account for roughly 60% of the enzymes used in industry and have high proteolytic activity, such as papain from Carica papaya latex and stem and fruit bromelains from the edible pineapple Ananas comosus. Objective: The wild pineapple Ananas ananassoides contains proteolytic enzymes, which motivated this study due to the potential applications of this type of enzyme. Methods: The fruit and stem of A. ananassoides were blended, clarified, and purified using chromatography (SP-Sepharose and Sephadex G-50). The molecular mass was determined using mass spectrometry (M.S.), and the N-terminal sequences were obtained and compared to other Bromeliaceae proteases. Fluorogenic substrates were used to determine the kinetic parameters. Results: As determined by M.S., the fruit and stem contain cysteine-peptidases with Mr of 27,329.6 and 23,912.5 Da, respectively, values that are very similar to those found in edible pineapple bromelains. Despite Mr and carbohydrate composition differences, both proteases have similar optimum pH values. They have similar temperature effects, though the stem protease is more thermally stable. Both proteases have a stronger preference for hydrophobic, polar, and basic residues. Both proteases hydrolyzed substrates containing polar and basic residues. Conclusion: A comparison of the N-terminal sequences (AVPQIIDW for fruit ananassains and AVPEIIDW for stem ananassains) reveals a high degree of homology when compared to other Bromeliaceae proteases such as papain.
Keywords: Bromeliaceae